There's no red roses where the oblivion lives - Francisco Herrera Rodríguez (Universidad de Alicante, 2015)
In this brief story, the author plunges us in the least constant rhetoric from reality: its ephemeral nature and sometimes vacant. Francisco Herrera weaves a narrative whose theme is the fragility of memory; or what it is even more forceful and almost daunting: the strength of oblivion. A call to reflect on the consequences in the life and death of human beings (the animal that walks upright with the fatuous pride its self-proclaimed status as rational), can have as much ability to oblivion.